SYSTEMATIC LITERATURE REVIEW : PENERAPAN METODE RESITASI BERPENDEKATAN OPEN-ENDED DALAM MENINGKATKAN HASIL BELAJAR DAN KEMAMPUAN KOMUNIKASI MATEMATIS - Hesti Yunitiara Rizqi; Anni Malihatul Hawa; Lisa Virdinarti Putra (JANACITTA, 2022)
Learning using the recitation method with an open-ended approach in this study is when the task is carried out outside the classroom so that students can construct their own knowledge and emphasize the process of how students can solve problems to the stage of an answer, not only focusing on the final result. This study aims to determine the effectiveness of the open-ended recitation method in improving learning outcomes and Â students' mathematical communication skills. This study uses a systematic literature review or also knownas a literature review. The method used for data collection techniques is to conduct a study to identify, assess, evaluate, and interpret research, literature books, and available reports. The journal articles collected are 25 journal articles published in the 2017-2021 time range. From various journal articles, the researcher collected journal articles related to the keywords in this study. Based on this research, it was found that the open-ended recitation method was not only able to improve mathematics learning outcomes but also to improve many mathematical abilities, especially students' mathematical communication skills.